The Longlasting Program Keluarga Harapan as Conditional Cash Transfer in Indonesia: The Existing Problems and the Policy Recommendations - Purba, Reniwan Agustina; Widianingsih, Ida; Muhtar, Entang Adhy (Borong Newinera Publisher, 2023)
Program Keluarga Harapan (PKH) is a conditional cash transfer program in Indonesia that requires beneficiaries to meet certain requirements such as school attendance and health checks. Adopted from similar models in Latin America, PKH aims to reduce short-term poverty and invest in the health and education of future generations. Since its launch in 2007, PKH has operated in various regions with different poverty and infrastructure issues. PKH faces several challenges, including mistargeting of beneficiaries and burdensome bureaucracy for the poor. To address this, improvements to the targeting system and simplification of document procedures are recommended. The program has also contributed to reducing stunting through improved nutrition and health education, although health facilities need to be improved. In the education sector, PKH has succeeded in increasing school enrollment and attendance, but has not significantly reduced child labor. In terms of livelihoods, PKH encourages beneficiaries to shift to non-agricultural jobs, although often only casual labor. This study uses descriptive and explanatory designs to describe and explain the evolution of the PKH policy from 2007. Descriptive design is used to describe policy changes that occurred during the period, while explanatory design is used to explain the factors that influence policy changes and their impact on program effectiveness. The results found that there were problems with PKH facilitators including insufficient numbers, high workloads, and low salaries, which affected their effectiveness. To improve the performance of facilitators, new recruitment, regular training, and increased salaries and working conditions are recommended.